Sensory evaluation and antibacterial activity of bee pollen extracts isolated from several stingless bees in two drying methods - NETTY MARIA NAIBAHO; HERIAD DAUD SALUSU; RUDITO RUDITO; BERNATAL SARAGIH; IRAWAN WIJAYA KUSUMA; WIDYA FATRIASARI; ENOS TANGKE ARUNG (Society for Indonesian Biodiversity, 2023)
Abstract. Naibaho NM, Salusu HD, Rudito, Saragih B, Kusuma IW, Fatriasari W, Arung ET. 2023. Sensory evaluation and antibacterial activity of bee pollen extracts isolated from several stingless bees in two drying methods. Biodiversitas 24: 2682-2688. This study aims to determine six stingless bee pollen extracts' sensory characteristics and antibacterial activity. The samples were dried using a chiller method at 4°C (14-22 days) and a 40°C oven (8-10 days). The sensory qualities of color, scent, taste, texture, and the antibacterial activity of six stingless bees were assessed while the bee pollen was drying. It was revealed for the first time that six bee pollen products from East Kalimantan had characteristics that were very close to what consumers preferred. The findings demonstrated that, compared to a 40°C oven, the 4°C chiller approach offered superior sensory value and antibacterial activity. Bee pollen Tetragonula reepeni (Friese, 1918) received the highest sensory score using the 4°C chiller method, scoring 4.81 (very like) for color and 3.71 (like) for taste. Bee pollen Tetragonula fuscobalteata (Cameron, 1908) received a score of 3.47 (like) for aroma, while the highest texture value was obtained by bee pollen Heterotrigona itama (Cockerell, 1918), scoring 4.19 (like very much). Bee pollen H. itama had the greatest sensory scores when using the 40°C oven method, scoring 3.58 (like), 3.22 (like), and 3.54 (like) for color, scent, and taste, and 3.69 (like) for texture. The antibacterial activity of the bee pollen extracts T. reepeni and Tetragonula iridipennis (Smith, 1854) achieved higher inhibition zone values when using the 4°C chiller method and 40°C oven method, with values ??of 15 mm, 16.00 mm, 14.33 mm, and 13.26 mm, respectively, for the bacterium Propionibacterium acnes NN657. The lowest Minimum Inhibitory Concentration (MIC) for antibacterial activity was 125 µL/mL for Staphylococcus aureus ATCC 25932, Staphylococcus epidermis NN349, Propionibacterium acnes NN357 and Escherichia coli ATCC 8742 of 250 µL/mL. Comparing the organoleptic characteristics of bee pollen, the chiller method at 4°C for 14 days retained quality attributes better than the bee pollen oven-drying method at 40°C.